Effect of chain extender on morphologies and properties of PBAT/PLA composites. (March 2023) - Sun, Jing; Huang, Anrong; Luo, Shanshan; Shi, Min; Song, Jiling; Luo, Heng
Biodegradable poly(butylene adipate-co-terephthalate)/poly(lactic acid) (PBAT/PLA) composites were prepared by melt blending, and chain extender was used to improve the compatibility of PBAT/PLA blends through the chemical reaction. The influence of PLA and chain extender contents on mechanical properties, morphology, and rheological properties of PBAT/PLA composites was systematically investigated. The results revealed that the Young's modulus and stress values gradually increased under the same strain, whereas the elongation at break decreased with the increase of chain extender content for PBAT/PLA (80/20) composites. Noteworthy, the presence of chain extender improves the interfacial compatibility between PLA and PBAT phases. At the chain extender content of 0.4, 0.6, and 0.8 wt.%, the extensional viscosity of the composites exhibited an increasing trend, whereas an obvious strain-hardening phenomenon emerged in the uniaxial extensional curves.